2016
DOI: 10.1111/tmi.12750
|View full text |Cite
|
Sign up to set email alerts
|

Results of clubfoot treatment after manipulation and casting using the Ponseti method: experience in Harare, Zimbabwe

Abstract: Abstractobjectives The objective of this study was to evaluate the outcomes of the Ponseti manipulation and casting method for clubfoot in a tertiary hospital in Zimbabwe and explore predictors of these outcomes.methods A cohort study included children with idiopathic clubfoot managed from 2011 to 2013 at Parirenyatwa Hospital. Demographic data, clinical features and treatment outcomes were extracted from clinic records. The primary outcome measure was the final Pirani score (clubfoot severity measure) after m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 29 publications
1
32
0
1
Order By: Relevance
“…The average number of castings used to correct the deformity was 6.5 times (range: 4 to 12). It was more than Pulak S. et al [21] (3 to 10 casts, average 4.9) but was less than Ponseti et al [24] (average 7.6 casts) and Tracey Smythe et al [23] (average 7.27 casts) studies. Morcuende [25] reported that 90.0% of the patients required five or fewer casts.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The average number of castings used to correct the deformity was 6.5 times (range: 4 to 12). It was more than Pulak S. et al [21] (3 to 10 casts, average 4.9) but was less than Ponseti et al [24] (average 7.6 casts) and Tracey Smythe et al [23] (average 7.27 casts) studies. Morcuende [25] reported that 90.0% of the patients required five or fewer casts.…”
Section: Discussionmentioning
confidence: 65%
“…11 (21.15%) cases presented within six weeks after birth and 34 (65.38%) cases within 6 months. In Tracey Smythe et al [23] previous family history was present in 10.5% cases. In our series, 38 (73.07%) patients required less than 8 casts for correction, with 2 patients requiring 12 casts.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The average number of castings used to correct the deformity was 6.41 times (range: 4 to 12). It was more than Pulak S. et al [21] (3 to 10 casts, average 4.9) but was less than Ponseti et al [24] (average 7.6 casts) and Tracey Smythe et al [23] (average 7.27 casts) studies. Morcuende [25] reported that 90.0% of the patients required five or fewer casts.…”
Section: Discussionmentioning
confidence: 65%
“…A Pirani score of 1 or less was achieved in 80.6% of feet. T. Smythe et al [23] achieved Pirani score of 1 or less in 85% of feet. J.…”
Section: Discussionmentioning
confidence: 99%